2009
DOI: 10.1183/09031936.00087908
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor air pollution is associated with disease severity in α1-antitrypsin deficiency

Abstract: The aim of this study was to determine whether long-term air pollution exposure is associated with clinical phenotype in a 1 -antitrypsin deficiency.In total, 304 PiZZ subjects underwent full lung function testing and quantitative high-resolution computed tomography to identify the presence and severity of the disease. Mean annual air pollutant data for 2006 was matched to the location of patients' houses and used in regression models to identify phenotypic associations with pollution, controlling for covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…We surmised that differences in elastin breakdown and subsequent anti-elastin generation might still occur between nonsmokers with and without AATD for this reason. This was not confirmed, perhaps because the effect sizes of agents other than cigarette smoke are small in both groups [22,23].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We surmised that differences in elastin breakdown and subsequent anti-elastin generation might still occur between nonsmokers with and without AATD for this reason. This was not confirmed, perhaps because the effect sizes of agents other than cigarette smoke are small in both groups [22,23].…”
Section: Discussionmentioning
confidence: 66%
“…This, together with the recent suggestion that smoking may be a risk factor for autoimmunity [12], is important to note in future studies of the prevalence of other autoantibodies in COPD and control populations. Subjects with AATD may be more sensitive to other environmental influences on lung function, as shown by relationships between outdoor air pollution and lung function in this group [22]. We surmised that differences in elastin breakdown and subsequent anti-elastin generation might still occur between nonsmokers with and without AATD for this reason.…”
Section: Discussionmentioning
confidence: 98%
“…Air pollution also induces lung inflammation10 and we have shown that ozone exposure related to lung function in a cross-sectional study of subjects with AATD in the UK 11. Other environmental agents, predominantly relating to occupation, may also influence lung function in AATD,12 13 but it is not known whether they influence lung function decline in this group.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the single-nucleotide polymorphisms (SNPs) were identified in the six haplotypes of the SERPINA1 gene, which controls synthesis of A1AT (Chappell, et al, 2006). Several environmental factors that accelerate the onset of symptoms in A1ATD patients, such as personal and second hand exposure to tobacco smoke in childhood, respiratory infections (Mayer et al, 2006), and higher exposures to ozone (Wood et al, 2009) have been also identified. In addition to the low circulating levels of A1AT in hereditary A1ATD, the risk of emphysema includes reduced antielastase activity.…”
Section: Introductionmentioning
confidence: 99%